2020
DOI: 10.3390/su12208519
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Students’ Experience with the Transition from Primary to Secondary School on Self-Regulated Learning and Motivation

Abstract: The transition from primary to secondary school is more successful when students’ learning is consistent. Students are also more likely to enjoy school, engage with learning, and have a high academic achievement in secondary school when they feel motivated. This is a critical aspect, especially in cases in which global pandemic situations allow only online schooling opportunities. Students that are away from school lack the traditional sources of motivation and self-regulated learning skills; thus, research is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 87 publications
(118 reference statements)
0
15
0
1
Order By: Relevance
“…Although we are dealing with differentiated constructs, looking at the effect sizes we found there does seem to be a strong interaction between self-regulatory skill and school engagement, at least in primary education students. In fact, according to Uka and Uka [71], both constructs appear to be relevant for successful school transitions. Primary school students with high self-regulated learning skills and emotional engagement might have a better experience when they move to secondary school.…”
Section: Discussionmentioning
confidence: 99%
“…Although we are dealing with differentiated constructs, looking at the effect sizes we found there does seem to be a strong interaction between self-regulatory skill and school engagement, at least in primary education students. In fact, according to Uka and Uka [71], both constructs appear to be relevant for successful school transitions. Primary school students with high self-regulated learning skills and emotional engagement might have a better experience when they move to secondary school.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed analyses of the data highlight that the STWT process depends on socio-demographic characteristics like gender (e.g., Daehlen, 2007;Struffolino & Borgna, 2021), personal decisions regarding school attendance, type of school, entering the labor market early or late (e.g., Boudon, 2016;Lucas, 2001), and skills and motivation (e.g., Pastore et al, 2021;Pinquart et al, 2003;Uka & Uka, 2020). In the countries of Southern and Eastern Europe, young women have a higher risk of becoming NEETs because of family responsibilities (see, e.g., Tosun et al, 2021).…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
“…Focusing on the 8 th grade students from four middle schools, Cai, Wang, Xu, & Zhou (2020) demonstrated that SRL of some subjects was evidently compelling under a particular pandemic period. Other researchers, Uka & Uka (2020), revealed that the student's experience with the transition from primary to secondary school might affect SRL and motivation. Involving physics students from five universities in Germany, Austria, and Croatia during the COVID-19 pandemic, Klein, Ivanjek, Dahlkemper, Jeličić, Geyer, Küchemann, & Susac (2021) discovered that a digital learning environment promoted academic achievement.…”
Section: Self-regulated Learning and Digital Learning Environment: Its' Effect On Academic Achievement During The Pandemicmentioning
confidence: 99%